Ideal Laws, Counterfactual Preservation, and the Analyses of Lawhood. Issue 3 (2nd July 2020) - Tan, Peter
ABSTRACT: This paper presents a unified argument against three widely held contemporary analyses of lawhood—Humean reductionism about laws, the dispositionalist view of laws, and the view of laws as relations between universals. I argue that it is a datum about the idealized laws of nature that they would be 'counterfactually preserved' if their idealizations had been true. But these three analyses of the laws all deliver the judgment that the ideal laws are not counterfactually preserved in the event of their idealizations' truth. For, as analyses of the property of lawhood, these views agree that the actual laws of nature (including the ideal laws) are constituted by non-ideal physical properties, relations, or regularities; hence, if the world had been physically ideal, what the laws ultimately amount to would have been different. I close by considering some alternative views of the laws of nature that do not have this implication, and I suggest that that is a reason to endorse them over these well-known analyses.